Melt inclusions in chassignite NWA 2737: A link between processes recorded in Martian meteorites and rocks at Gale crater. (10th July 2021) - Wu, Peiyu; Gazel, Esteban; Udry, Arya; Setera, Jacob B.; Ostwald, Amanda
Abstract: Northwest Africa (NWA) 2737, one of the only three discovered Martian chassignites, provides critical constraints on the evolution of the Martian mantle and crust. Because of chassignites' cumulative nature, they contain abundant melt inclusions (MI). MI are small droplets of melts trapped by crystals during the cooling of magma. They are critical to the study of pre‐eruptive parental magma compositions, and thus, provide snapshots of the composition and evolution of Martian magmatic systems. Here, we present fractional crystallization models using parental magma composition calculated from NWA 2737 melt inclusions as starting compositions. We used the thermodynamic modeling software MELTS to model fractional crystallization of NWA 2737 parental magma compositions with a wide range of parameters (pressure, water content, oxygen fugacity). Our models show that the felsic compositions recently analyzed at the Martian surface in Gale crater, especially Sparkle and Angmaat, the two rocks thought to be analogous to the earliest continental crust on Earth, can be obtained by fractional crystallization of chassignite‐like parental melts. Our results suggest a link between the processes that resulted in chassignites and the rocks analyzed in situ at Gale crater. To assess the possible scenarios for Martian magma migration and storage processes, we compared chassignites to terrestrial analogs formed via various mechanisms and proposed two mechanisms that may explain the intrusive and effusive rocks found in situ at Gale crater: (1) emplacement and fractionation in a closed‐system crustal reservoir and (2) eruption of mafic to intermediate lavas of a relatively open system subject to constant replenishment.